Experimental evaluation of anti-stripping additives on porous asphalt mixtures - Abdullah, Mohd Ezree; Mohd Shukry, Nurul Athma; Abdul Hassan, Norhidayah; Hainin, Mohd Rosli; Mohamed Abdullah, Nor Asniza; Mahmud, Mohd Zul Hanif; Putrajaya, Ramadhansyah; Mashros, Nordiana (PENERBIT UTM PRESS, 2016)
The open structure of porous asphalt mix influences its strength and durability against air, water and clogging materials. These factors cause loss of adhesion between binder-aggregate interface and loss of cohesion within the binder film. This could lead to stripping problem which contribute to premature failures as well as deterioration in the performance and service life of porous asphalt. Therefore, this study is aimed to evaluate the potential of diatomite as anti-stripping additives in porous asphalt and compared with hydrated lime and Ordinary Portland Cement (OPC). Field Emission Scanning Electron Microscopy (SEM) test and Energy Dispersive X-ray Spectroscopy analysis (EDX) were conducted to investigate the microstructure and chemical composition of the anti-stripping additives. A number of gyratory compacted samples of porous asphalt mixture with Malaysian gradation were prepared. Each sample was incorporated with 2% of anti-stripping additives as filler then mixed with polymer modified bitumen of PG76. The samples were measured for air voids content, permeability rate, resilient modulus and abrasion loss. The results indicate that samples prepared with hydrated lime show higher permeability rate and lower abrasion loss compared to samples with OPC and diatomite. However, the samples prepared with diatomite show enhanced resilient modulus compared to those with hydrated lime and OPC.